Staying healthy - Schaefer, A. R. (Adam Richard), 1976- (Chicago : Heinemann Library, 2010)
Introduces children to the importance of being healthy and having good hygiene habits, and discusses exercise, a good diet, washing hands, tooth care, getting enough sleep, and more.
Staying healthy -- Exercise and good food -- Keeping clean -- Washing hands -- Staying clean -- Tooth care -- Being careful of germs -- Wearing the right clothes -- Being careful outdoors -- Keeping your mind healthy -- Getting enough sleep -- Getting started on a healthy life.
Includes bibliographical references (p. 31) and index.
Library Media Connection
Science and Children (N.S.T.A.)
Wilson's Children
Library Media Connection, January 2010
Science and Children (N.S.T.A.), November 2009
Keywords: Exercise -- Juvenile literature; Health -- Juvenile literature; Hygiene -- Juvenile literature; Exercise; Health; Hygiene; Exercise; Health; Hygiene